1995
DOI: 10.1111/j.1600-079x.1995.tb00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in edible plants identified by radioimmunoassay and by high performance liquid chromatography‐mass spectrometry

Abstract: Melatonin, the chief hormone of the pineal gland in vertebrates, is widely distributed in the animal kingdom. Among many functions, melatonin synchronizes circadian and circannual rhythms, stimulates immune function, may increase life span, inhibits growth of cancer cells in vitro and cancer progression and promotion in vivo, and was recently shown to be a potent hydroxyl radical scavenger and antioxidant. Hydroxyl radicals are highly toxic by-products of oxygen metabolism that damage cellular DNA and other ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
647
1
15

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 961 publications
(666 citation statements)
references
References 26 publications
3
647
1
15
Order By: Relevance
“…Although we and others have consistently detected appreciable quantities of melatonin in plants both by chromatography and immunological methods [Van Tassel et al, 1993;Kolar and Machackova, 1994;Dubbels et al, 1995;Hattori et al, 1995;Kolar et al, 1995;Manchester et al, 2000], we argue here that neither method is reliable on its own.…”
Section: Isolation and Parallel Variationcontrasting
confidence: 59%
See 3 more Smart Citations
“…Although we and others have consistently detected appreciable quantities of melatonin in plants both by chromatography and immunological methods [Van Tassel et al, 1993;Kolar and Machackova, 1994;Dubbels et al, 1995;Hattori et al, 1995;Kolar et al, 1995;Manchester et al, 2000], we argue here that neither method is reliable on its own.…”
Section: Isolation and Parallel Variationcontrasting
confidence: 59%
“…By this method, we have found melatoninlike immunoreactivity in P. nil, Arabidopsis, tobacco cotyledons/leaves, tomato fruit, black tea, coffee, red and white wines, mushrooms, and the unicells Spirulina and baker's yeast [Van Tassel, 1997]. Melatonin values have been published for a number of other angiosperm species, also based on RIA or HPLC [Dubbels et al, 1995;Hattori et al, 1995].…”
Section: Isolation and Parallel Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1995, two groups independently found that melatonin indeed exists in plants including fruits, vegetables and cereals. 4,5 Thereafter, numerous publications have confirmed melatonin's presence in the plant kingdom. [6][7][8][9] It seems that melatonin's presence in plants is a universal phenomenon.…”
Section: Introductionmentioning
confidence: 99%